The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1250/ast.29.139
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal and elevation localization of two sound sources using interaural phase and level differences

Abstract: Sound source localization and signal segregation using a small number of microphone elements is expected in not only multimedia products but also in daily-use products, such as hearing aids. The frequency domain binaural model can localize a sound source and segregate signals coming from a specific direction using two input signals. In this paper, a method of two sound sources localization in azimuth and elevation using interaural phase and level differences is proposed. The performance of this localization is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Currently, we are testing and evaluating this algorithm [15] with the physical realization (humanoid robot head) from Fig. 1.…”
Section: Preliminary Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, we are testing and evaluating this algorithm [15] with the physical realization (humanoid robot head) from Fig. 1.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…While searching for the most suitable model for horizontal and vertical signal localization in humanoid robots, we implemented a promising binaural model [14] Block diagram of the binaural model of Chisaki et al [15]. The input signal consists of the left and the right audio channels of the two ears.…”
Section: Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chisaki et al 4 suggest to give more importance to bins with higher signal energy because a higher SNR can be expected for those. COMPaSS uses a similar weighting of the frequency bins based on signal energy and the achieved similarity values.…”
Section: Filter Scoring and Extractionmentioning
confidence: 99%
“…It was developed especially for speech sources and has been used as a front end for a speech recognition system. 7 Chisaki et al 4 showed that FDBM is capable to localize two concurrent sound sources in azimuthal and elevation direction with high accuracy.…”
Section: Compared Algorithmsmentioning
confidence: 99%